Growth, structural change and regional inequality in Malaysia - Asan Ali Golam Hassan (Ashgate Pub., 2004)
Economic development in the long run is seen as a process of structural change that is affected by economic growth. Malaysia is one of the middle-income economies that are going through rapid structural change.